The Responsibility of Transboundary Haze Pollution: The Case of Wildfire in Canada - Gunawan, Yordan; Hafsari, Dhayu Ajeng; Khasanah, Pentanita Uswatun; Arumbinang, Mohammad Hazyar (Arena Hukum, 2024)
Responsibility for losses other countries suffer due to haze pollution is a serious issue. Transboundary haze pollution responsibility is related to the impact of smog pollution in one country and negatively impacts other countries in the vicinity. A country should take responsibility for forest fires out of respect for the country and its citizens. One example is the forest fires in Canada that spread smoke to neighbouring countries. This involves cooperation between countries to reduce the risk of transboundary haze pollution. This article used qualitative descriptive research methods. Qualitative descriptive research methods seek to answer the "what," "how," or "why" questions related to the phenomenon under study. The aim is to understand the research subject deeply and not generalise the results to the wider population. This research article concludes the principle of state responsibility, which essentially contains the obligation of states that have an impact on other countries to make reparation to the aggrieved country and restore the condition of the concerned country. In Canada, there were frequent forest fires in previous years, causing haze that spread to various countries. By understanding the consequences of forest fires and haze spread, Indonesia should enhance its prevention and management strategies by adopting approaches from Canada's forest fire management. The Trail Smelter case serves as a benchmark for addressing haze pollution, and Canada's experience offers valuable lessons for Indonesia, which also faces similar wildfire risks.